Immunocytochemical assessment of FKBP51 and Glucocorticoid receptor localization in asthmatic patients - Alsaffar, Sura F.; Yenzeel, Jabbar H.; Ghazi, Haider Faisal (Iraqi Journal of Science, 2019)
Asthma is a chronic inflammatory disease affecting 5% of the world population. FKBP51 is an important immunophilin modular protein of the glucocorticoid receptor (GC).The aim of the present study was to evaluate the levels and immunocytochemical distribution of FKBP51 and GR in lymphocyte cells of asthmatic patients, by use of immunocytochemistry method, and to assesslevels ofstress hormones (cortisol and ACTH) by radioimmuniassay (RIA).The results showed significantly increased nuclear localization and decreasedcytoplasmic distribution of FKBP51, while they showed a significant increase in nuclear localization and a non-significant decrease in cytoplasmic distribution of GRin asthmatic patients(P<0.05).Cortisol and ACTH levels were also measured and showedinsignificant increases(P<0.05)in steroid treated (338.85 ±139.5 mMol/L, 35.05±3.77 ng/ml, respectively)and non steroid treated asthmatics(280.5 ± 74.6 mMol/L, 32.0±6.43 ng/ml, respectively)as compared with the control group (234.33±29.13 mMol/L, 29.0±7.02 ng/ml, respectively).